Estudo comparativo in vitro do preparo do canal radicular com instrumentos protaper® acionados manualmente e movidos a motor empregando a tomografia computadorizada de feixe cônico - cone beam - Heringer, Nevelton (2009)
This work aimed to evaluate in vitro, by means cone beam computed tomography, the action of endodontic instruments ProTaper® NiTi manually operated and motor driven with continuous rotation in the apical segment, to three millimeters of the surface external root apex of the mesiobuccal root of human maxillary molars. To this purpose, 20 teeth were used and randomly distributed into two groups. In group I were used 10 root canals using the instruments manually operated. In group II were used 10 mesiobuccal root canals instrumented with engine powered instruments with continuous rotation, making use of the electric motor X-Smart™ with speed of 250rpm applying to each instrument torque (N.cm) recommended by the manufacturer. The teeth were numbered and fixed trough their crowns on a proper support for maintaining the position when undergoing to radiation of cone beam by iCAT scanner before and after the preparation. The wear was assessed by comparing the thickness of dentin before and after preparation as measured by the distance between the root canal wall and the outer surface of the root, in the buccal, palatal, mesial and distal surfaces, apical segment mentioned above, using a ruler to measure from Gimp 2.6.6 software. According to the obtained results, the wear rendered with the manual technique (Group I) was lower compared to the technique of continuous rotation (Group II), although with no statistical significance, however, the ProTaper® NiTi instruments for hand use had showed a larger wear for the buccal side, statistically significant (p <0.05) when compared with the engine-driven instruments. Therefore, it was conclude that the ProTaper® NiTi endodontic instruments used in continuous rotation were more effective and set the root canal in a more centralized way than the hand instruments and that the latter were statistically (p <0.05) less safe than the first with respect to apical displacement. The cone beam computed tomography proved to be a promising tool as a methodological recourse to analyze the root canal preparation, although it needs further study and improvement of its management for this purpose.